(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The present study aimed to develop an ethosomal gel loaded with Dalbergia sissoo leaves extract for transdermal application. Materials and Methods: D. sissoo extract was subjected to phytochemical analysis, flavonoid content, total phenolic content, and Fourier-Transform Infrared Spectroscopy analysis. The ethosomes containing D. sissoo extract were formulated and characterized based on morphology, particle size, surface charge, and encapsulation efficiency. Subsequently, the optimized ethosomes were incorporated into Carbopol gel and then evaluated for organoleptic properties, pH, viscosity, and skin permeation. Results and Discussion: Dalbergia extract incorporated in the ethosomes showed spherical shape, vesicle size (143 nm), −14.9 mV surface charge, and good entrapment efficiency (84.4%). The optimized formulation was further incorporated into Carbopol gel and showed optimal pH (6.2), good spreadability, high release percentage (85.92%), as well as stability over 60 days. Conclusion: The findings revealed that the ethosomal gel loaded with D. sissoo leaves extract was found to be a potential strategy for effective delivery.